Efficiency of Jeruju (Acanthus illicifolius) as a Bioindicator of Copper Pollution in Surabaya Mangrove Waters - Wulandari, Adelia; Agustina, Eva; Hadi, Irfan; Tyastirin, Esti; Irawanto, Roni (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2025)
Environmental pollution, especially heavy metal contamination, has become a major threat to aquatic ecosystems. This study aimed to investigate the efficiency of Jeruju (Acanthus illicifolius) as a bioindicator and phytoremediator of copper (Cu) pollution in mangrove waters of Surabaya. Sampling was conducted in three locations: Gunung Anyar Tambak, Surabaya Mangrove Botanical Garden, and Wonorejo Mangrove. Each location consisted of two sampling points: dock and estuary. Water and Jeruju leaf samples (upper, middle, and lower parts) were analyzed for Cu concentration using Atomic Absorption Spectroscopy (AAS). Environmental parameters were also measured. The results showed that Cu concentration in water samples was very low and only detected at Gunung Anyar dock (0.001 ppm). However, Cu accumulation in Jeruju leaves varied, with the highest concentration (3.16 ppm) found in lower leaves at Gunung Anyar dock. The correlation between water quality parameters, particularly pH and TDS, and Cu concentration indicated that Jeruju can effectively accumulate Cu and serve as a potential phytoremediator and bioindicator in polluted Mangrove ecosystems.